2021
DOI: 10.15578/squalen.514
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds, Cosmeceutical And Nutraceutical Applications of Green Seaweed Species (Chlorophyta)

Abstract: Seaweeds are valuable marine plants that have garnered much attention from the public due to their high bioactive, nutrients and minerals content. Seaweeds have been used in multiple applications, including in cosmeceutical, nutraceutical and pharmaceutical industries. Nevertheless, this review will focus on the bioactive compounds of Chlorophyta and their potential application in nutraceutical and cosmeceutical industries. Chlorophyta are believed to possess a significant amount of nutrients and minerals, suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Accordingly, Senni et al [155] suggested its potential role in prevention of photoaging of the skin. Consequently, fucoidan acts as an inhibitor of tyrosinase and reduces skin pigmentation, while used in skin-whitening formulation [156,157]. Pereira [158], Carvalho and Pereira [159], and Gesztesi et al [160] suggested ulvan as desirable raw material for cosmeceuticals.…”
Section: Porphyra Umbilicalismentioning
confidence: 99%
“…Accordingly, Senni et al [155] suggested its potential role in prevention of photoaging of the skin. Consequently, fucoidan acts as an inhibitor of tyrosinase and reduces skin pigmentation, while used in skin-whitening formulation [156,157]. Pereira [158], Carvalho and Pereira [159], and Gesztesi et al [160] suggested ulvan as desirable raw material for cosmeceuticals.…”
Section: Porphyra Umbilicalismentioning
confidence: 99%
“…Hence, alternative biofertilizers, that are more environment-friendly is needed in the future [3]. Seaweed or marine macroalgae are considered to be a critical renewable resource that has gained much attention due to their multiple applications such as pharmaceutical, cosmeceutical, and nutritional aspects [4]; [5]. This may represent an alternative option to conventional fertilizer.…”
Section: Introductionmentioning
confidence: 99%